Default of Banking Credit Agreements in the Time of Covid 19 - Sri Dewi; Sriono Sriono; Elviana Sagala (Budapest International Research and Critics University, 2021)
The covid 19 pandemic resulted in a very significant economic impact, and resulted in many defaults on bank credit agreements which underwent payment restructuring based on the covid 19 virus. Financial Services Authority (OJK) Regulation No. 11/POJK.03/2020 concerning the national economic stimulus as a countercyclical policy for the impact of the spread of covid 19 gives authority to banks to establish policies that support economic growth stimulus for debtors affected by the spread of covid 19, one of which is credit or financing restructuring policies. The occurrence of a national disaster caused by the Covid 19 virus had an impact on the force majeure situation. That defaults due to the spread of the covid-19 virus have resulted in debtors being negligent in carrying out their obligations, this method uses the normative juridical method, which refers to the provisions of positive laws and regulations in Indonesia. The results of the research show that defaults in the credit agreement cannot be used as an excuse for not fulfilling their obligations. The spread of covid-19 cannot be used as an excuse that causes a compelling situation that requires the debtor to commit an act of default. In the concept of a rule of law, judicial power is independent in carrying out its judicial function, thus enabling the exercise of judicial power to be fair in examining, adjudicating and deciding cases based on law and justice. Then the policy of the regulations issued by the government against the spread of the covid-19 virus is very important for the community regarding the problem of the spread of the covid-19 virus.